The association between parity and hypertension: a cross-sectional, community-based study - Musa, Imad R.; Osman, Osman E.; Adam, Ishag (Frontiers in Cardiovascular Medicine, 2023)
Background: The available data on the association between parity and hypertension are inconclusive. This study was conducted to investigate the prevalence of hypertension and its association with parity among adult Sudanese women. Methods: A multi-stage sampling survey was conducted in four villages in the River Nile State in Sudan between July and September 2022. The World Health Organization's three-level stepwise questionnaire was used to gather the participants' sociodemographic characteristics (age, sex, marital status, parity, educational level, occupation, obstetric history, family history of hypertension, weight and height). Regression analyses were performed. Results: A total of 408 women were recruited. The median (measured in terms of interquartile range [IQR]) age was 45.0 years (33.0‒55.7 years). A linear regression analysis revealed a significant association between parity and diastolic blood pressure (coefficient, 0.60; P = 0.011). The prevalence of hypertension (55.9%) increased with parity and ranged from 43.7% to 74.9%. In the multivariate analyses, increasing age (adjusted odds ratio [AOR], 1.03; 95% confidence interval [CI], 1.02‒1.05), increasing parity (AOR, 1.09; 95% CI, 1.01‒1.19), family history of hypertension (AOR, 1.79; 95% CI, 1.15‒2.77), and increasing body mass index (AOR, 1.09; 95% CI, 1.05‒1.13) were associated with hypertension. In women of ages ≥ 50 years, increasing parity was significantly associated with hypertension (AOR, 1.15; 95% CI, 1.2‒1.29). Para > 5 (AOR, 2.73; 95% CI, 1.11‒6.73) was associated with hypertension. Conclusion: A high prevalence of hypertension was found among Sudanese women, and that parity at 5 or more is linked to hypertension. .